600 Pahang State secondary school students joined YES! Rock The School Mega Edition Pahang - Nor Salwana, Mohammad Idris (UMPSA, 2024)
GAMBANG, 27 July 2024 - A total of 600 secondary school students from across Pahang camped for two days at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) to participate in the YES! Rock The School Mega Edition: Pahang event organized by Talent Corporation Malaysia Berhad (TalentCorp).